A method for purification of intracellular protein. - Tey, Beng Ti; Chew, Few Ne; Tan, Wen Siang (2009)

(untitled)
The present specification discloses an integrated purification technique for purifying recombinant intracellular protein (GFP) from intact E. coli cells using preparative PAGE column. Under the influence of electric fields, the negatively charged GFP was drifted out from cells without the need of cell disruption process. The electrophoresed cells were observed under SEM and some on the membrane of cells were observed. GFP was then separated from other host cells host protein along polyacrylamide gel and finally eluted electrophoretically from the gel. The invention has successfully recovered the GFP with purity and yeild 95% and 82%, respectively in 100 min operation.